PENGGUNAAN HUMOR DALAM DAKWAH KOMUNIKASI ISLAM - Wandi Wandi (fakultas Ushuluddin dan Dakwah IAIN Bone, 2020)
AbstractThe use of humor in da'wah of Islamic communication is something that is widely practiced by some preachers whether it is through religious pulpits or through the internet media called social media, humor is aimed to attract the attention of the audiences and be a part that is always awaited by the audiences in da’wah even though in fact, humor is only a complement in an Islamic da’wah, which is nothing else but to get attention from the audiences. However, the use of humor in the da'wah of Islamic communication sometimes backfires for those who do not pay attention to the standard criteria of humor such as ethical and aesthetic. Thus, based on the results of the analysis of the author that the use of humor in da’wah of Islamic communication is permissible and it becomes a good way as long as the preacher observes that in slipping his humor, he does not forget the propriety set out in the Qur'an and hadith. Keywords: humor, da’wah, Islamic communication